An in vivo study evaluating lesion sterilization and tissue repair 3 MIX-MP noninstrumentation endodontic treatment as an alternative to conventional endodontic retreatment - Vaishnavi Dasari; Sohani Maroli; Likhitha Chowdary; Ravikumar Karukola; Srinath Hunsur Premakumar; Vinay Vusurumarthi (Wolters Kluwer Medknow Publications, 2016)
Aim: To alleviate the patient's symptoms and promote periapical healing in teeth with failure of root canal treatment, without the removal of previous obturating material using lesion sterilization and tissue repair (LSTR) 3 MIX-MP noninstrumentation endodontic treatment (NIET). Materials and Methods: Fifteen single-rooted teeth with a history of root canal treatment 1-2 years previously, requiring retreatment, with pain, sinus tract, swelling and periapical lesions, and having acceptable obturation were included in the study. The previous coronal restoration was removed, and a medication cavity was prepared for placement of 3MIX MP; this was followed by lining with Glass ionomer cement and a coronal restoration with composite resin. Results: At 8 weeks, all patients did not have either pain, tenderness on vertical percussion, pain on biting, or swelling (asymptomatic). Radiographically, the periapical lesions had reduced by 1 mm in five cases. In six patients, the lesion size remained unchanged. Conclusion: LSTR NIET is an excellent, inexpensive, less traumatic, and least time-consuming alternative to treat symptomatic teeth requiring endodontic retreatment.